Cutaneous excreta of the earthworm Eisenia fetida (Haplotaxida: Lumbricidae) might hinder the biological control performance of entomopathogenic nematodes. (February 2020) - Chelkha, Maryam; Blanco-Pérez, Rubén; Bueno-Pallero, Francisco Ángel; Amghar, Souad; El Harti, Abdellatif; Campos-Herrera, Raquel
Abstract: Earthworms enhance soil structure, the decomposition of organic matter and the dissemination of beneficial soil organisms such as the entomopathogenic nematodes (EPNs). Nevertheless, the effects of earthworm feeding behavior or cutaneous excreta (CEx) on the performance of EPNs as biological control agents is poorly understood. We hypothesized that the presence of earthworms or their excreta reduces EPN fitness, measured in terms of pathogenicity and reproductive success. In laboratory experiments we first evaluated the killing ability of EPNs against Galleria mellonella (Lepidoptera: Pyralidae) larvae when inoculated in autoclaved soil alone or in combination with the earthworm Eisenia fetida (Haplotaxida: Lumbricidae) or their excreta. We also evaluated EPN efficacy and reproduction when exposed to CEx derived from E. fetida at two nematode concentrations (1.5 and 10 IJs/cm 2 ). For both experiments, we tested four steinernematids ( Steinernema carpocapsae, S. feltiae, S. glaseri, and S. khuongi ) and two heterorhabditids ( Heterorhabditis bacteriophora and H. zealandica ). The presence of earthworms or their excreta resulted in significant reduction of the larval mortality caused by some of the steinernematids at certain timings depending of the species ( P < 0.015), while heterorhabditids were mainly not affected. Both S. feltiae and H. zealandica progeny production was significantly reduced ( P < 0.01) when exposed to CEx. Hence, we showed that the presence of CEx might alter the biocontrol performance of certain EPN species, especially steinernematids bigger than 600 μm in size ( S. feltiae, S. glaseri, and S. khoungi ), by affecting their pathogenicity and reproductive success. Highlights: Cutaneous excreta (CEx) of earthworms might interfere with entomopathogenic nematode activity. Entomopathogenic nematodes are affected by CEx in a species-specific manner. The CEx of Eisenia fetida did not affect heterorhabditids nematode pathogenicity. The CEx of Eisenia fetida compromised steinernematids nematodes pathogenicity. The fitness of certain steinernematids (>600 μm size) is reduced by CEx.